Hierarchical porous carbon-coated cathode material, lithium ion battery and preparation method

By using hierarchical porous carbon-coated cathode materials, the capacity and cycle performance issues of lithium-ion battery cathode materials were solved, and the high conductivity and stability of the materials were improved. This also improved lithium-ion diffusion and electrolyte wetting, thereby enhancing the electrochemical performance of the battery.

CN117393725BActive Publication Date: 2026-11-06XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311446047.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-02
Publication Date
2026-11-06
Estimated Expiration
2043-11-02

AI Technical Summary

Technical Problem

Existing technologies struggle to effectively improve the specific capacity, rate performance, and cycle performance of lithium-ion battery cathode materials. In particular, the long Li+ diffusion path in single-crystal cathode materials leads to poor reaction kinetics and low capacity.

Method used

A hierarchical porous carbon-coated cathode material is used, in which micropores, mesopores and macropores are formed by carbon coating layers doped with nitrogen and phosphorus. Combined with organic amine etching and calcination processes, a cathode material with optimized pore structure is prepared.

Benefits of technology

It improves the conductivity and active sites of the material, shortens the lithium-ion diffusion path, improves the reversible capacity, cycle stability and rate performance of the battery, and alleviates the material expansion phenomenon.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117393725B_ABST
    Figure CN117393725B_ABST
Patent Text Reader

Abstract

This invention provides a hierarchical porous carbon-coated cathode material, a lithium-ion battery, and a preparation method thereof. The hierarchical porous carbon-coated cathode material includes a coating layer and a core. The core includes the cathode material. The coating layer is a nitrogen- and phosphorus-doped carbon coating layer with a hierarchical pore structure comprising micropores, mesopores, and macropores. The micropores account for 57.1–87.2% of the pore volume, the mesopores account for 7.6–38.1%, and the macropores account for 0.8–35.3%. Carbon coating improves the electronic conductivity and lithium-ion conductivity of the material. The hierarchical porous structure of the carbon coating layer promotes charge accumulation, effectively shortens the lithium-ion diffusion path, and reduces lithium-ion migration resistance, thereby improving rate performance and enhancing the capacity utilization and cycle performance of the cathode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, and particularly to a graded porous carbon-coated cathode material, a lithium-ion battery, and a preparation method thereof. Background Technology

[0002] With the rapid development of modern technology, batteries, as a key component of energy storage, play a vital role in various industries. Lithium-ion secondary batteries, due to their advantages such as high rate capability, high voltage, and high specific energy, have become a key area for the development of my country's new energy industry. Compared to polycrystalline cathode materials, monocrystalline cathode materials have larger grain sizes, therefore Li... + The longer diffusion path results in poorer reaction kinetics and lower capacity.

[0003] Surface carbon coating is one of the most important methods for improving the specific capacity, rate performance, and cycle performance of lithium batteries. Currently, there are two common carbon coating methods: one involves adding carbon powder to the raw materials in a certain proportion, mixing them evenly, and then reacting them under a high-temperature reducing atmosphere; the other involves adding organic compounds to the cathode material or its precursor, reacting them under a high-temperature reducing atmosphere, causing the organic matter to pyrolyze and generate carbon, forming a carbon coating on the material surface. Typically, organic compounds containing only carbon, hydrogen, and oxygen are used for carbon coating to ensure that no other impurity atoms are mixed in. However, current technologies struggle to achieve optimal coating results.

[0004] It should be noted that the information disclosed in the background section above is only used to enhance the understanding of the background of the present invention, and therefore may include information that does not constitute prior art known to those skilled in the art. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a graded porous carbon-coated cathode material, a lithium-ion battery, and a preparation method thereof.

[0006] According to a first aspect of the present invention, a hierarchical porous carbon-coated cathode material is provided, comprising a coating layer and a core, wherein the core comprises a cathode material, the coating layer is a nitrogen- and phosphorus-doped carbon coating layer, the coating layer having a hierarchical pore structure comprising micropores, mesopores and macropores, wherein the pore volume ratio of the micropores is 57.1-87.2%, the pore volume ratio of the mesopores is 7.6-38.1%, and the pore volume ratio of the macropores is 0.8-35.3%, wherein the pore volume ratio is the proportion of the corresponding pore volume in the total pore volume of the coating layer.

[0007] In an exemplary embodiment of the invention, the cathode material is selected from lithium cobalt oxide cathode materials, multi-element cathode materials, or lithium iron phosphate cathode materials.

[0008] In an exemplary embodiment of the invention, the pore size of the micropore is D1, the pore size of the mesopore is D2, and the pore size of the macropore is D3, wherein D1 ≤ 2nm; 2nm <D2≤50nm;50nm<D3≤140nm。

[0009] In one exemplary embodiment of the invention, the total pore volume per unit mass of the carbon coating is a, where a > 0.004 cm³. 3 / g.

[0010] In an exemplary embodiment of the invention, the specific surface area BET value of the core before carbon coating is X, and the specific surface area BET value of the hierarchical porous carbon-coated cathode material after carbon coating is Y, wherein X and Y satisfy: 5m 2 / g<YX<40m 2 / g.

[0011] In an exemplary embodiment of the invention, the oil absorption value of the graded porous carbon-coated cathode material is 3.5 to 16 ml / 100g.

[0012] According to a second aspect of the present invention, a method for preparing a hierarchical porous carbon-coated cathode material as described in any one of the above claims is provided, characterized in that it comprises:

[0013] S1, the positive electrode material is dispersed in a solvent to obtain a dispersion, and amino-containing monomers, aldehyde-containing monomers and phosphorus-containing monomers are added to the dispersion. The pre-coated positive electrode material is obtained through a condensation polymerization reaction.

[0014] S2, an organic amine is added to the pre-coated cathode material and etched to obtain an intermediate;

[0015] S3, the intermediate is calcined to obtain a hierarchical porous carbon-coated cathode material.

[0016] In an exemplary embodiment of the invention, in step S1, the amino-containing monomer, the aldehyde-containing monomer, and the phosphorus-containing monomer are dissolved in a solvent to obtain an amino-containing monomer solution, an aldehyde-containing monomer solution, and a phosphorus-containing monomer solution. First, the amino-containing monomer solution is added to the dispersion, then the aldehyde-containing monomer solution is added dropwise, and finally the phosphorus-containing monomer solution is added.

[0017] And / or, in step S1, the concentration of the positive electrode material in the dispersion is 1-3 g / L;

[0018] And / or, in step S1, the reaction temperature of the condensation polymerization reaction is 15-40°C, and the reaction time is 10-20h.

[0019] In an exemplary embodiment of the invention, the amino-containing monomer is selected from one or more of 3,3'-diaminobenzidine, melamine, and 1,3,5-tris(4-aminophenyl)benzene; and / or, the aldehyde-containing monomer is selected from one or both of terephthalaldehyde and 1,3,5-trialdehydebenzene; and / or, the phosphorus-containing monomer is selected from DOPO; and / or, the organic amine is selected from one or more of ethylenediamine, propylamine, and aniline.

[0020] In an exemplary embodiment of the invention, in step S2, the pre-coated positive electrode material is dispersed in a solvent to obtain solution A, the organic amine is mixed with the solvent to prepare solution B, and solution B is added to solution A, so that the concentration of organic amine in the reaction system is 0.01-0.08 mol / L and the reaction time is 13-24 h.

[0021] In an exemplary embodiment of the invention, in step S3, calcination is carried out under inert gas protection at a temperature of 600–800°C for 2–4 hours.

[0022] According to a third aspect of the present invention, a lithium-ion battery is provided, comprising: a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode comprises a hierarchical porous carbon-coated positive electrode material as described in any one of the preceding claims.

[0023] The beneficial effects of the hierarchical porous carbon-coated cathode material, lithium-ion battery, and preparation method of the present invention are as follows:

[0024] The hierarchical porous carbon-coated cathode material provided by this invention has a coating layer doped with nitrogen and phosphorus elements, which effectively improves the conductivity of the material, increases active sites, and increases the defect concentration in the material, thus contributing to the material's specific capacity. Through organic amine etching, the coating layer simultaneously incorporates micropores, mesopores, and macropores. The micropores and mesopores facilitate electrolyte permeation and promote charge accumulation; the mesopores and macropores effectively reduce lithium-ion diffusion paths, allowing lithium ions to penetrate the carbon layer and contact the matrix, effectively improving the material's rate performance. Simultaneously, it alleviates the expansion phenomenon that occurs during battery operation. Furthermore, the structure of the carbon coating layer avoids direct contact between the material and the electrolyte, improving the material's cycle stability. The aforementioned hierarchical porous carbon coating structure effectively improves the reversible capacity, cycle stability, and rate performance of the cathode material in the battery.

[0025] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and are not intended to limit this disclosure. Attached Figure Description

[0026] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this disclosure and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0027] Figure 1 This is a schematic diagram of the structure of the hierarchical porous carbon-coated cathode material obtained in an embodiment of the present invention.

[0028] Figure 2 This is a flowchart illustrating the preparation process of the hierarchical porous carbon-coated material according to an embodiment of the present invention.

[0029] Figure 3 The diagram shows the cycle performance of the cathode materials obtained in Examples 1-3 and Comparative Examples 1-4 of this invention. Detailed Implementation

[0030] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions in the embodiments of this disclosure will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0031] The following provides a detailed description of the hierarchical porous carbon-coated cathode material, lithium-ion battery, and preparation method according to embodiments of the present invention.

[0032] Please see Figure 1 This invention provides a hierarchical porous carbon-coated cathode material, comprising a coating layer 20 and a core 10. The coating layer 20 coats the outside of the core 10 and is a nitrogen- and phosphorus-doped carbon coating layer. The coating layer 20 has a hierarchical pore structure, including micropores, mesopores, and macropores. The pore volume ratio of micropores is 57.1%–87.2%, the pore volume ratio of mesopores is 7.6%–38.1%, and the pore volume ratio of macropores is 0.8%–35.3%. The pore volume ratio refers to the proportion of the corresponding pore volume in the total pore volume of the coating layer. For example, the pore volume ratio of micropores is the ratio of the total micropore volume to the total pore volume of the coating layer. By forming a hierarchical pore structure with different pore sizes, it is beneficial to improve conditions such as lithium ion release and electrolyte wetting, effectively enhancing the electrochemical performance of the material.

[0033] Furthermore, in one embodiment, the pore volume ratio of the micropores is 60-86%. The higher pore volume ratio of the micropores indicates a greater number of micropores, which is beneficial for ensuring the structural stability of the coating layer, as well as the full wetting of the electrolyte and the accumulation of charge, resulting in better cycle performance.

[0034] Further, in one of the embodiments, the pore volume proportion of mesopores is 13 to 37%. On the one hand, mesopores are conducive to electrolyte penetration and charge accumulation, and on the other hand, they help to increase the ion diffusion rate. When the pore volume of mesopores is kept within the above range, both the reversible capacity and rate performance of the material are better.

[0035] Further, in one of the embodiments, the pore volume proportion of macropores is 1 to 5%. This further optimizes the ion diffusion path, and the relatively small pore volume of macropores prevents the inner core from excessive contact with the electrolyte, thus improving the material stability and cycle performance.

[0036] In one embodiment, the pore diameter of micropores is D1, where D1 ≤ 2 nm. The pore diameter D1 of micropores is the smallest, which can be, for example, 0.1 nm, 0.5 nm, 1 nm, 2 nm and so on.

[0037] In one embodiment, the pore diameter of mesopores is D2, where 2 nm < D2 ≤ 50 nm. The pore diameter of mesopores is moderate, which can be, for example, 3 nm, 10 nm, 20 nm, 40 nm and so on.

[0038] In one embodiment, the pore diameter of macropores is D3, where 50 nm < D3 ≤ 140 nm.

[0039] The pore diameter D1 of micropores is the smallest, which can be, for example, 0.1 nm, 0.5 nm, 1 nm, 2 nm and so on. The pore diameter D2 of mesopores is moderate, which can be, for example, 3 nm, 10 nm, 20 nm, 40 nm and so on. The pore diameter D3 of macropores is 60 nm, 80 nm, 100 nm, 120 nm, 140 nm and so on.

[0040] It should be noted that the pore diameters of a plurality of micropores may be the same or different. Similarly, the pore diameters of a plurality of mesopores may be the same or different, and the pore diameters of a plurality of macropores may be the same or different. The pore diameters of micropores, mesopores and macropores are adjusted through different etching processes. The pore volume proportions of micropores, mesopores and macropores can be measured by a specific surface area and pore size analyzer, for example, a Best BSD-A6B6M specific surface area and pore size analyzer can be used for analysis and measurement. The adsorption-desorption curve is collected. Based on the different pore channel structures of micropores, mesopores and macropores, the instrument program automatically selects points reasonably for fitting calculation according to different theoretical calculation models, so as to obtain the pore volumes of micropores, mesopores and macropores.

[0041] In one of the embodiments, the positive electrode material of the inner core is selected from lithium cobalt oxide positive electrode materials, multi-element positive electrode materials, lithium iron phosphate positive electrode materials and the like.

[0042] In one embodiment, the total pore volume per unit mass of carbon coating is 'a', and the total pore volume satisfies: a ≥ 0.004 cm⁻¹ 3 / g. For example, the total pore volume a of the coating layer is 0.005 cm³. 3 / g, 0.006cm 3 / g, 0.01cm 3 / g, 0.02cm 3 / g etc. The coating layer has sufficient porosity to ensure lithium ion transport and adequate electrolyte wetting.

[0043] In one embodiment, the specific surface area BET value of the core before carbon coating is X, and the specific surface area BET value of the hierarchical porous carbon-coated cathode material after carbon coating is Y, where X and Y satisfy: 5m 2 / g<YX<40m 2 / g. Furthermore, 7m 2 / g<YX<39m 2 / g; more preferably, 25m 2 / g<YX<39m 2 / g. The coated material has a higher specific surface area than the uncoated cathode material, providing more active sites and reaction surfaces, thus significantly improving the electrochemical performance of the material.

[0044] In one embodiment, the oil absorption value of the hierarchical porous carbon-coated cathode material is 3.5–16 ml / 100g. Further, the oil absorption value is 5–13.57 ml / 100g, and more preferably, it is 11–13.1 ml / 100g. Maintaining the oil absorption value within the above range results in better performance stability.

[0045] It should be noted that in this embodiment, the oil absorption value can be determined according to the method in GB / T 3780.2-2007-Carbon Black-Part 2: Determination of Oil Absorption Value.

[0046] Please refer to Figure 2 The present invention also provides a method for preparing the above-mentioned hierarchical porous carbon-coated cathode material, comprising:

[0047] S1, the positive electrode material is dispersed in a solvent to obtain a dispersion, amino-containing monomer, aldehyde-containing monomer and phosphorus-containing monomer are added to the dispersion, and a pre-coated positive electrode material is obtained through condensation polymerization reaction;

[0048] S2, an organic amine is added to the pre-coated cathode material and etched to obtain an intermediate;

[0049] S3, the intermediate is calcined to obtain a hierarchical porous carbon-coated cathode material.

[0050] In one embodiment, in step S1, the solvent used for the dispersion can be methanol, ethanol, acetone, etc. The step of adding the amino-containing monomer, aldehyde-containing monomer, and phosphorus-containing monomer to the dispersion includes: dissolving the amino-containing monomer, aldehyde-containing monomer, and phosphorus-containing monomer separately in a solvent such as ethanol solution to obtain an amino-containing monomer solution, an aldehyde-containing monomer solution, and a phosphorus-containing monomer solution; first adding the amino-containing monomer solution to the dispersion; after a first reaction time; then adding the aldehyde-containing monomer solution dropwise; after a second reaction time; and finally adding the phosphorus-containing monomer solution to continue the reaction.

[0051] Specifically, the first and second reaction times are preferably 1 to 4 hours, such as 2 hours or 4 hours. The first and second reaction times can be the same or different. By adding amino-containing monomers, aldehyde-containing monomers, and phosphorus-containing monomers one by one to carry out the reaction, it is beneficial to form a uniform and stable coating layer structure.

[0052] In one embodiment, the amino-containing monomer is selected from one or more of 3,3'-diaminobenzidine, melamine, and 1,3,5-tris(4-aminophenyl)benzene. Further, the amino-containing monomer is preferably 3,3'-diaminobenzidine.

[0053] In one embodiment, the aldehyde-containing monomer is selected from one or both of terephthalaldehyde and 1,3,5-trialdehydebenzene. Further, terephthalaldehyde is preferred as the aldehyde-containing monomer.

[0054] In one embodiment, the phosphorus-containing monomer is selected from DOPO. DOPO is a novel flame retardant intermediate with the following structural formula:

[0055] In one embodiment, in step S1, the concentration of the positive electrode material in the dispersion is 1 to 3 g / L.

[0056] In one embodiment, in step S1, the reaction temperature of the condensation polymerization reaction is 15–40°C, and the reaction time is 10–20 h. Further, after the condensation polymerization reaction is completed, the reaction product is collected by centrifugation, then washed with ethanol, and dried under vacuum at 60°C to obtain a pre-coated cathode material. This pre-coated cathode material is a cathode material coated with a phosphorus-nitrogen doped polymer, which has an aldehyde-amine condensation structure.

[0057] Specifically, in one embodiment, when the ammonia-containing monomer is selected from 3,3'-diaminobenzidine and the aldehyde-containing monomer is selected from terephthalaldehyde, the structural formula of the coating layer of the pre-coated positive electrode material is shown in formula (I):

[0058] In one embodiment, step S2, the step of adding an organic amine to the pre-coated cathode material for etching, specifically includes: dispersing the pre-coated cathode material in a solvent such as ethanol to obtain solution A; mixing the organic amine with the solvent such as ethanol to prepare solution B; adding solution B to solution A, such that the concentration of the organic amine in the reaction system is 0.01–0.08 mol / L; and the reaction time is 13–24 h. After the reaction is completed, the product is collected by centrifugation, then washed with ethanol, and vacuum dried to obtain an intermediate.

[0059] In one embodiment, in step S2, the organic amine is selected from one or more of ethylenediamine, propylamine, and aniline. More preferably, the organic amine is selected from propylamine. The intermediate obtained by etching with the organic amine is a hierarchical porous polymer-coated cathode material.

[0060] In one embodiment, the pre-coated cathode material with a coating layer as shown in structural formula (I) is etched with an organic amine, and its structural formula is shown in formula (II) or (III):

[0061]

[0062] The polymer network structure coated on the surface of the pre-coated cathode material consists of numerous imine bonds (C=N) formed by the condensation of aldehyde and amino groups. These imine bonds are dynamically reversible. By adding a guest organic amine, an exchange reaction occurs through the competition between the primary amine (-NH2) and the aldehyde group. The aldehyde group reacts with the guest primary amine, and the multi-arm monomer containing the amino group leaves, thus controlling the pore size of the coating layer. The etching degree of the coating layer is affected by the concentration of the guest primary amine molecules and the etching time. By adjusting the concentration of the organic amine and the etching time, the hierarchical pore structure of the coating layer can be modified.

[0063] In one embodiment, step S3 includes calcining the intermediate under an inert gas atmosphere at a temperature of 600–800°C for 2–4 hours.

[0064] This invention also provides a lithium-ion battery, comprising: a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode comprises the aforementioned hierarchical porous carbon-coated positive electrode material. The lithium-ion battery may further include a separator between the positive and negative electrodes. It is understood that lithium-ion batteries can be manufactured using known methods in the prior art.

[0065] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0066] Example 1

[0067] This embodiment provides a hierarchical porous carbon-coated cathode material, obtained by the following steps:

[0068] (1) Disperse 100g of uncoated NCM cathode material in 500mL of ethanol and stir to make it evenly dispersed to obtain NCM dispersion.

[0069] (2) Weigh 4.8g of 3,3'-diaminobenzidine, 6g of terephthalaldehyde, and 2.4g of DOPO, and dissolve them separately in ethanol solutions to prepare 10g L... -1 Solution a, solution b, and solution c.

[0070] (3) Under stirring conditions at room temperature, solution a was first slowly added to the NCM dispersion. After 2 hours, solution b was slowly added dropwise to the above solution. After reacting for 2 hours, solution c was slowly added dropwise. After reacting for another 12 hours at room temperature, the mixture was centrifuged at 9000 rpm. -1 Centrifugation was performed to obtain a solid. The centrifuged product was washed twice with ethanol and dried in a vacuum oven at 60°C for 24 hours to obtain a phosphorus-nitrogen doped polymer-coated cathode material.

[0071] (4) Disperse 100g of the product obtained in step (3) in 500mL of ethanol to obtain dispersion a. Dissolve propylamine in 50mL of ethanol solution and add it to the above dispersion a to make the concentration of propylamine in the system 0.04mol / L. Stir the reaction at room temperature for 18h and then separate it with a centrifuge to obtain the centrifuged product. Wash the centrifuged product twice with ethanol and dry it in a vacuum oven at 60℃ for 24h to obtain the hierarchical porous carbon-coated cathode material.

[0072] (5) The product obtained in step (4) is placed in a quartz tube furnace and heated to 600°C for 4 hours under Ar protection to obtain a graded porous carbon layer coated cathode material.

[0073] Example 2

[0074] This embodiment provides a hierarchical porous carbon-coated cathode material, which differs from Example 1 in that: in step (4), the reaction is stirred at room temperature for 14 hours.

[0075] Example 3

[0076] This embodiment provides a hierarchical porous carbon-coated cathode material, which differs from Example 1 in that: in step (4), the reaction is stirred at room temperature for 22 hours.

[0077] Comparative Example 1

[0078] This comparative example provides a method for preparing a cathode material, which is the uncoated NCM cathode material in Example 1.

[0079] Comparative Example 2

[0080] This comparative example provides a hierarchical porous carbon-coated cathode material, obtained according to the following steps:

[0081] (1) Disperse 100g of uncoated NCM cathode material in 500mL of ethanol and stir to make it evenly dispersed to obtain NCM dispersion.

[0082] (2) Weigh 4.8g of 3,3'-diaminobenzidine, 6g of terephthalaldehyde, and 2.4g of DOPO, and dissolve them separately in ethanol solutions to prepare 10g L... -1 Solution a, solution b, and solution c.

[0083] (3) Under stirring conditions at room temperature, solution a was first slowly added to the NCM dispersion. After 2 hours, solution b was slowly added dropwise to the above solution. After reacting for 2 hours, solution c was slowly added dropwise. After reacting for another 12 hours at room temperature, the mixture was centrifuged at 9000 rpm. -1 Centrifugation was performed to obtain a solid. The centrifuged product was washed twice with ethanol and dried in a vacuum oven at 60°C for 24 hours to obtain a phosphorus-nitrogen doped polymer-coated cathode material.

[0084] (4) The product obtained in step (3) is placed in a quartz tube furnace and heated to 600°C for 4 hours under Ar protection to obtain a graded porous carbon layer coated cathode material.

[0085] Comparative Example 3

[0086] This comparative example provides a hierarchical porous carbon-coated cathode material, which differs from Example 1 in that: in step (4), the concentration of propylamine in the system is 0.01 mol / L.

[0087] Comparative Example 4

[0088] This comparative example provides a hierarchical porous carbon-coated cathode material, which differs from Example 1 in that: in step (4), the concentration of propylamine in the system is 0.08 mol / L, and the reaction is stirred at room temperature for 24 h.

[0089] Test case

[0090] The cathode materials obtained in Examples 1-3 and Comparative Examples 1-4 were used as test samples for electrochemical performance testing, as detailed below:

[0091] The test sample was ground uniformly with conductive agent SP and binder PVDF at a mass ratio of 96.5:1.5:2. An appropriate amount of NMP was then added to form a slurry, which was uniformly coated onto pretreated aluminum foil. Under the same conditions, CR2032 coin cells were prepared using conventional methods. The electrochemical cycle performance of the prepared coin cells was tested at 45°C, with a charge / discharge rate of 0.5C / 1C and a voltage range of 2.8-4.45V. The cycle performance test results are as follows: Figure 3 As shown in Table 1, the capacity performance and rate performance test results are as follows.

[0092] Table 1

[0093]

[0094] from Figure 3 As shown in Table 1, the hierarchical porous carbon-coated material obtained in this embodiment exhibits higher capacity, better rate performance, and better cycle performance compared to the uncoated cathode material. By controlling the concentration of organic amines and etching time in the system, microporous, mesoporous, and macroporous structures with different pore volume ratios can be obtained. When the following conditions are met: the pore volume ratio of micropores is 57.1–87.2%, the pore volume ratio of mesopores is 7.6–38.1%, and the pore volume ratio of macropores is 0.8–35.3%, the rate performance and cycle performance of the cathode material are effectively improved.

[0095] The embodiments described above are some, but not all, of the embodiments of this disclosure. The detailed description of the embodiments of this disclosure is not intended to limit the scope of the claimed disclosure, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this disclosure without inventive effort are within the scope of protection of this disclosure.

Claims

1. A method for preparing a hierarchical porous carbon-coated cathode material, characterized in that, include: S1, the positive electrode material is dispersed in a solvent to obtain a dispersion, and amino-containing monomers, aldehyde-containing monomers and phosphorus-containing monomers are added to the dispersion. The pre-coated positive electrode material is obtained through a condensation polymerization reaction. S2, an organic amine is added to the pre-coated cathode material and etched to obtain an intermediate; S3, calcining the intermediate to obtain a graded porous carbon-coated cathode material; The amino-containing monomer is selected from 3,3'-diaminobenzidine, the aldehyde-containing monomer is selected from terephthalaldehyde, the phosphorus-containing monomer is selected from DOPO, and the organic amine is selected from propylamine.

2. The preparation method according to claim 1, characterized in that, In step S1, the amino-containing monomer, the aldehyde-containing monomer, and the phosphorus-containing monomer are dissolved in a solvent to obtain an amino-containing monomer solution, an aldehyde-containing monomer solution, and a phosphorus-containing monomer solution. First, the amino-containing monomer solution is added to the dispersion, then the aldehyde-containing monomer solution is added dropwise, and finally the phosphorus-containing monomer solution is added. And / or, in step S1, the concentration of the positive electrode material in the dispersion is 1~3 g / L; And / or, in step S1, the reaction temperature of the condensation polymerization reaction is 15~40℃, and the reaction time is 10~20 h.

3. The preparation method according to claim 1, characterized in that, In step S2, the pre-coated positive electrode material is dispersed in a solvent to obtain solution A. The organic amine is mixed with the solvent to prepare solution B. Solution B is added to solution A so that the concentration of organic amine in the reaction system is 0.01~0.08 mol / L and the reaction time is 13~24 h.

4. The preparation method according to claim 1, characterized in that, In step S3, calcination is carried out under inert gas protection at a temperature of 600-800℃ for 2-4 hours.

5. The preparation method according to claim 1, characterized in that, The coating layer of the pre-coated cathode material is a phosphorus-nitrogen-doped polymer, which has an aldehyde-amine condensation structure. The structural formula of the phosphorus-nitrogen-doped polymer is shown in formula (I): (I); And / or, the coating layer of the intermediate is a polymer with a hierarchical porous structure, the structural formula of which is shown in formula (II) or (III): (II); (III)。 6. A hierarchical porous carbon-coated cathode material, characterized in that, The coating, prepared by any one of claims 1 to 5, comprises a coating layer and a core, wherein the core comprises a positive electrode material, the coating layer is a nitrogen- and phosphorus-doped carbon coating layer, and the coating layer has a hierarchical pore structure comprising micropores, mesopores, and macropores, wherein the pore volume ratio of the micropores is 57.1-87.2%, the pore volume ratio of the mesopores is 7.6-38.1%, and the pore volume ratio of the macropores is 0.8-35.3%, wherein the pore volume ratio is the proportion of the corresponding pore volume in the total pore volume of the coating layer.

7. The hierarchical porous carbon-coated cathode material according to claim 6, characterized in that, The cathode material is selected from lithium cobalt oxide cathode materials, multi-element cathode materials, or lithium iron phosphate cathode materials.

8. The hierarchical porous carbon-coated cathode material according to claim 6, characterized in that, The pore size of the micropore is D1, the pore size of the mesopore is D2, and the pore size of the macropore is D3, wherein D1 ≤ 2nm; 2nm < D2 ≤ 50nm; 50nm < D3 ≤ 140nm.

9. The hierarchical porous carbon-coated cathode material according to claim 6, characterized in that, The total pore volume per unit mass of the carbon coating is 'a', where 'a' > 0.004 cm³. 3 / g.

10. The hierarchical porous carbon-coated cathode material according to claim 6, characterized in that, The specific surface area BET value of the core before carbon coating is X, and the specific surface area BET value of the hierarchical porous carbon-coated cathode material after carbon coating is Y. X and Y satisfy: 5 m 2 / g<YX<40 m 2 / g.

11. The hierarchical porous carbon-coated cathode material according to claim 6, characterized in that, The oil absorption value of the graded porous carbon-coated cathode material is 3.5~16 ml / 100 g.

12. A lithium-ion battery, characterized in that, include: A positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode comprises a hierarchical porous carbon-coated positive electrode material as described in any one of claims 6 to 11.

Citation Information

Patent Citations

  • Lithium iron phosphate coated with monatomic loaded nitrogen-phosphorus co-doped carbon composite material as well as preparation method and application of lithium iron phosphate

    CN114388802A